Exploring the role of color in packaging design product: children’s cereal box / Muhammad Idham Zaidi - Zaidi, Muhammad Idham (2023)
The purpose of this academic work is to demonstrate how colour is crucial to the branding of a children's cereal box in terms of packaging design. The use of colour serves to convey a product's intended messages while also influencing young consumers' perception and behavior. When utilized to distinguish products on shelves, boost brand identification, and even influence customer buying behavior, colours can stimulate specific emotions and connections in both consumers and children, such as trust, enthusiasm, or relaxation. The current study offers a thorough analysis of packaging design. It goes into detail into the function of colour, the psychology of colour, and visuals in product packaging and sales. Since it is widely believed that graphics and colour play significant roles in boosting product sales, colour should be given a lot of care in packaging design. The consequences for producers, marketers, practitioners, and researchers are covered in length, and there are also suggestions for additional research.